Finger sweating levels evaluated by video capillaroscopy system are increased in patients with systemic sclerosis compared to pre-clinical stage patients - Jinnin, Masatoshi; Tani, Sayaka; Mikita, Naoya; Fujii, Takao; Furukawa, Kanako; Tabata, Kayoko; Okuhira, Hisako (Drug Discoveries & Therapeutics, 2020)
New strategies for early diagnosis and careful follow-up of systemic sclerosis are urgently needed. We unconventionally used a video capillaroscopy system to measure the amount of sweating on finger pads, and investigated its clinical significance. Thirty-three Japanese patients who were diagnosed with typical or pre-clinical stage patients of systemic sclerosis were included in this study. Five healthy subjects were also included. Among twenty-one patients with typical systemic sclerosis that fulfilled ACR/EULAR 2013 classification criteria, seven had increased sweating levels. On the other hand, among twelve pre-clinical stage patients that did not fulfill the classification criteria, no patient showed increase in finger sweating. We found that there was statistically significant difference. The ratio of diffuse cutaneous systemic sclerosis was also found to be significantly higher in subjects with increased amounts of sweating than in subjects with normal levels. Furthermore, the positivity of topoisomerase I antibody was statistically higher in patients with increased sweating levels than in those without. These results indicated that measurement of finger sweating levels may be a useful tool for early diagnosis and clarification of pathogenesis in this disease.